Hyponatremia in children with lower respiratory tract infection: a cross-sectional study - Thani, Kamal Prasad; Shrestha, Sandeep; Gautam, Uttara; Keshari, Munna (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Lower respiratory tract infections (LRTIs) are leading cause of pediatric mortality in Nepal. Hyponatremia is common electrolyte imbalance in severe infections, but its prevalence and impact in high-altitude, resource-limited settings like Jumla are poorly characterized. This study aimed to determine prevalence and clinical significance of hyponatremia in children hospitalized with LRTIs.Methods: Hospital-based cross-sectional study was conducted from January 2024 to June 2025, including 80 children aged 1 month to 12 years with LRTIs. Serum sodium levels were measured, and hyponatremia was classified as mild (130-134 mEq/L), moderate (125-129 mEq/L), or severe (